Dryland Conservation Technologies: Enhancing Agricultural Profitability and Sustainability - Havlin, John L; Schlegel, Alan J (Annals of Arid Zone, 2016)
The adoption of dry land conservation technologies can significantly increase productivity and profitability in dry land agriculture. These technologies are based on maintaining surface residue cover and conserving as much water as possible' for use by marketable crops. Dryland conservation technologies involve: (i) reducing soil water evaporation; (ii) eliminating water use by weeds, (iii) reducing water runoff (and soil erosion), (iv) increasing water infiltration, and (v) increasing snow catch. These critical components involve maintaining crop residues on the soil surface throughout the year. Although storing additional water is essential, changing the cropping system to utilize the additional water will dramatically increase prolitability. Therefore, producers must reduce tillage intensity to increase the quantity of soil water stored; however, to increase profitability producers must reduce their dependency on fallow by increasing their cropping intensity with alternative spring and summer row crops. As a result of interdisciplinary technology transfer programmes, the number of acres managed with conservation technologies has increased live-fold over the last five years. Producers understand that the dry land conservation technologies provide the greatest opportunity to achieve agricultural sustainability and profitability in the Great Plains.